2023
DOI: 10.2147/jmdh.s403045
|View full text |Cite
|
Sign up to set email alerts
|

Blood Profiles in the Prediction of Radioiodine Refractory Papillary Thyroid Cancer: A Case–Control Study

Abstract: Purpose Although most patients with papillary thyroid cancer can be cured by surgery and I-131 ablation, a small proportion will progress to radioactive iodine refractory (RAIR) thyroid cancer. The prediction of RAIR in its early stages can improve patient prognosis. The aim of this article is to evaluate the blood biomarkers in patients with RAIR and to establish a prediction model. Patients and Methods Data collected from patients with thyroid cancer that were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…In our recent study on serum malondialdehyde concentration in PTC patients undergoing RAI, increased oxidative stress was demonstrated throughout the treatment procedure [18][19][20]. It has also been suggested that blood markers can predict early-stage RAI refractory PTC [21][22][23][24][25][26]. Our hypothesis was that there must be a relationship between oxidative stress and both the presence of PTC and distinct clinical management, including RAI.…”
Section: Introductionmentioning
confidence: 83%
“…In our recent study on serum malondialdehyde concentration in PTC patients undergoing RAI, increased oxidative stress was demonstrated throughout the treatment procedure [18][19][20]. It has also been suggested that blood markers can predict early-stage RAI refractory PTC [21][22][23][24][25][26]. Our hypothesis was that there must be a relationship between oxidative stress and both the presence of PTC and distinct clinical management, including RAI.…”
Section: Introductionmentioning
confidence: 83%
“…The BRAF V600E mutation has been claimed to be a risk factor for recurrent RAI-R metastases of PTC in a number of studies ( 12 , 16 , 44 , 45 ). In our previous work, we also obtained similar results in subjects exposed to radiation in childhood who lived in the northern regions of Ukraine most affected by the Chornobyl accident ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 5-15% of differentiated thyroid carcinomas may be insensitive to RAI therapy (8)(9)(10). The RAI-refractory (RAI-R) tumors may be a life-threatening condition reducing a 5-year disease-specific survival rate to 60-70% (11,12), and a 10-year survival rate to as low as 10-20% for patients with RAI-R metastatic malignancies (6,(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation